MITIGATING HEAVY METAL POLLUTION IN CAR BATTERY WORKSHOP SOILS: A CASE STUDY USING XRF ANALYSIS - Osman, Christina; Hassan, L; Amel Daniel, (International Journal of Allied Sciences (IJAS), 2022)
A previous investigation [1] used X-ray fluorescence (XRF) technique to study soil pollution in car battery workshops situated within residential neighborhoods. To further this research, this article examines a different car battery workshop in Khartoum state where surface soil is regularly removed and replaced. Our findings reveal a substantial reduction in lead, iron, and copper concentrations compared to the initial study. The average concentrations of these heavy metals are 2.0x104, 3.9x104, and 86.2 ppm, respectively. This case study underscores the value of proactive soil management in minimizing heavy metal pollution in car battery workshops and its potential positive impact on nearby residential communities.